The struggle for constitutional monarchy in the khanate of khiva at the beginning of the xx century - Alikhanov, Mukhammadjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
There is written the political processes which taken place in the Khiva Khanate in the early twentieth century in this article. Article describes about trying to implement the constitutional monarchic system by young Khivans and these reforms impact, and about the influence of the Interim Government and the Russian military on the basis of various historical sources and archival materials.